The use of sunflower lecithin in the technology on gluten-free bread with enzymatic modification of flour starch - Medvid, Irina; Shydlovska, Olena; Dotsenko, Viktor (My University, 2018)
The necessity of search of new ways to improve the quality of gluten-free bread for people suffering from celiac disease is considered in the article. As one of the directions of this problem solution the use of surface-active substances has been suggested. The efficiency of the use of sunflower skimmed lecithin for production of rice bread with the use of enzymatic modification of flour starch has been proved. Its influence on the intensity of fermentation in the rice dough, the activity of fermentative microflora and the change of specific volume in the process of maturation has been investigated. The positive influence of emulsifier in the technology of rice bread on the indicators as ready-made products, in particular specific volume, porosity and elastic properties of the crumb have been studied out. It established that the addition of sunflower skimmed lecithin to vegetable oil in the process of production of rice bread using flour starch hydrolysis promotes the extension of its shelf life and freshness.
Keywords: сeliac disease; rice bread; gluten; surface-active substances; lecithin; starch; enzymatic modification; целіакія; рисовий хліб; глютен; лецитин; крохмаль; ферментативна модифікація; поверхнево-активні речовини; кафедра готельно-ресторанної справи